Gender Differences in the Effect of Employee-Manager Friendships on Salary Dynamics in CPA Firms - Yossef Tobol; Ronen Bar-El; Yuval Arbel; Ofer H. Azar (Institute of Labor Economics (IZA), 2019)
We study the effect of employee-manager relations on salary increases. We use data obtained from a longitudinal survey, carried out among auditing team members in leading Israeli CPA firms (which are subsidiaries of American firms). Our main findings suggest that the degree of friendship with the team manager is positively correlated with the rate of the salary increase, particularly among female workers whose team manager is also a female. We also find that upon being hired to the job, male workers gain a higher return to experience compared with female workers.
Keywords: C33; D03; J31; J71; 330; CPA; friendship; gender salary gap; wage determination